The Contemporary Drawings themed ‘Dimension 100: Space and Time’ in conjunction with the 100 years celebration of the establishment of Sultan Idris Education University, Malaysia - Mokhtar, Elis Syuhaila; Mahsan, Ida Puteri; Mat Il, Izani; Mat Salleh, Nor Syazwani (Journal of Humanities and Social Sciences (JHASS), 2021)
Kertas ini membentangkan empat hasil karya lukisan projek tahun akhir bertemakan ‘Dimensi 100: Ruang dan Masa’ bagi penganugerahan Ijazah Sarjana Muda Pendidikan (Seni) dengan Kepujian, Jabatan Seni dan Reka Bentuk (JSRB), Universiti Pendidikan Sultan Idris (UPSI). Tema ini dipilih bersempena sambutan 100 tahun penubuhan UPSI. Bagi memenuhi kriteria projek, pelajar dikehendaki menghasilkan karya melalui tema yang diberi di samping meneroka kaedah-kaedah baharu yang dapat membawa perubahan kepada kelaziman studio lukisan secara kreatif dan inovatif. Kajian ini berfokus kepada empat orang pelajar major studio lukisan yang telah melaksanakan penyelidikan praktis studio melalui tiga fasa utama iaitu perkembangan idea, proses penghasilan karya, seterusnya persembahan karya. Dapatan kajian menunjukkan pelajar berjaya mensintesiskan tema melalui penghasilan empat buah karya lukisan kontemporari dalam bentuk eksperimentasi yang merentas disiplin bidang sains, seni persembahan, muzik dan tarian, fotografi, videografi, serta kemahiran digital sejajar dengan arus kemajuan teknologi terkini. Pameran virtual telah dilangsungkan secara talian menggunakan platform Artsteps. Karya-karya ini merupakan artifak yang dapat mencerminkan kebitaraan bakal guru seni kelahiran UPSI sebagai universiti pendidikan nombor satu di Malaysia. The Contemporary Drawings themed ‘Dimension 100: Space and Time’ in conjunction with the 100 years celebration of the establishment of Sultan Idris Education University, Malaysia Abstract: This paper presents four drawings with the theme of ‘Dimension 100: Space and Time’ from the final year project of Bachelor in Art Education (with Honours), Department of Art and Design (JSRB), Sultan Idris Education University (UPSI). This theme was chosen in conjunction with the 100 years celebration of the establishment of UPSI. The project criteria required students to produce series of drawings which related to the given theme as well as to creatively explore the new mediums and techniques that could bring ‘changes’ to the practice of drawing studio innovatively. This paper focuses on four students from the major of drawing studios who have carried out the studio practice research through three main phases, namely the development of ideas, the process of producing work, finally, and finally, the presentation of work. The findings found that the students have successfully synthesized the themes into the production of four contemporary drawings in the form of experimentation works which are crossed disciplines of science, performing arts, music and dance, photography, videography, and digital through the latest technology influences. The virtual exhibition was held online using the Artsteps platform. These works are the artifacts that can reflect the uniqueness of UPSI’s art teachers as the number one educational university in Malaysia. Keywords: Contemporary Drawings, Studio Practice, UPSI 100 Years Theme.